Seroprevalence of IgG Antibodies against Echinococcus granulosus in the Population of the Region of Thessaly, Central Greece - Fotiou, Vasilios (Public Library of Science, 2012)
Echinococcosis notification rate in Greece, based on the most recent data, is below 0.25 per 100,000 population. To further investigate the epidemiology of echinococcosis in Greece a study was designed to determine the seroprevalence of Echinococcus granulosus antibodies in the population of Thessaly, Central Greece. Five hundred and forty two left over blood samples in Thessaly laboratories, were collected using a stratified convenient sampling procedure. Samples were analyzed with enzyme linked immunosorbent assay. The seropositivity found was 1.1%(95% C.I., 0.5–2.5), with 5 out of 6 seropositive results to be in the age group of over 65 (OR = 17.95, 95%CI 2.04–157.11, p value 0.009). Rural residence was also found as a risk factor to seropositivity (RR = 7.60, 95% CI 0.89–64.64, p value 0.039). Surveillance data and our study results converge that echinococcosis is being reduced in Greece, with older population to be affected mostly. These might be due to the disease transmission restriction, by the control measures being implemented. Efforts should be continued, in both animals and humans side, by increasing training campaigns and public awareness.